Pengembangan Media TAKALTAR (Tabel Perkalian Pintar) Materi Perkalian Kelas III di SD Negeri Mendo Barat - Inge Oktafianti; Muhamad Sofian Hadi (CENDEKIAWAN, 2025)
The purpose of this research is to develop TAKALTAR media (Smart Multiplication Table) for valid and practical multiplication material for third grade students in Elementary School. This research is research and development which uses the Bord and Gall model consist of 10 stages which include: potential and problems, data collection, product design, design validation, design revision, product testing, product revision, usage testing, product revision and mass production. The data collection techniques and instruments use interviews, questionnaires, and documentation. The data analysis techniques are an analysis of expert validation data and analysis of student response data. The subjects of this research were all the students in the third grade at SD Negeri 18 Mendo Barat with 30 students consisting of 13 female students and 17 male students. The expert assessment shows that TAKALTAR media (Smart Multiplication Table) is valid and practical as a learning medium by making revisions based on expert advice. The percentage of validity given by material experts 1 is 80% (feasible), by material experts 2 is 88% (very feasible) and by media experts are 90% (feasible). Practical percentages given from the results of media trials (small scale) get a percentage of 100% (very practical) and the results of media use tests (large scale) get a percentage of 99% (very practical). Then it can be concluded that the TAKALTAR media (Smart Multiplication Table) that has been developed is valid and practical is used as a learning media.